2012
DOI: 10.1136/bmj.e7666
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reducing total fat intake on body weight: systematic review and meta-analysis of randomised controlled trials and cohort studies

Abstract: Objective To investigate the relation between total fat intake and body weight in adults and children.Design Systematic review and meta-analysis of randomised controlled trials and cohort studies. Inclusion criteria Randomised controlled trials and cohort studies of adults or children that compared lower versus usual total fat intake and assessed the effects on measures of body fatness (body weight, body mass index, or waist circumference) after at least six months (randomised controlled trials) or one year (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
169
0
13

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(186 citation statements)
references
References 76 publications
4
169
0
13
Order By: Relevance
“…43 These outcomes were assessed in studies of durations ranging from 6 months to more than 8 years, and in both children and adults; despite this heterogeneity, similar trends were reported. 43 A meta-analysis of data from 57,735 participants in these trials revealed that a low total dietary fat intake is linked to a reduction in body weight (-1.6 kg) versus a normal fat intake. Baseline fat intakes ranged from 28% to 43% of total energy, and decreasing fat intake in participants with a low baseline fat intake was associated with additional weight loss relative to controls.…”
Section: Meta-analyses and Systematic Reviewsmentioning
confidence: 83%
“…43 These outcomes were assessed in studies of durations ranging from 6 months to more than 8 years, and in both children and adults; despite this heterogeneity, similar trends were reported. 43 A meta-analysis of data from 57,735 participants in these trials revealed that a low total dietary fat intake is linked to a reduction in body weight (-1.6 kg) versus a normal fat intake. Baseline fat intakes ranged from 28% to 43% of total energy, and decreasing fat intake in participants with a low baseline fat intake was associated with additional weight loss relative to controls.…”
Section: Meta-analyses and Systematic Reviewsmentioning
confidence: 83%
“…Different nutrients are known to influence different pathways of energy balance. For example, dietary fiber may directly modulate appetite or may also have metabolic effects on fat breakdown and storage [4], while ingested fat is very efficiently stored in fat cells and is characterized by a high palatability facilitating energy over-consumption [5]. Depending on the combined intake of these and other nutrients, either synergistic or antagonistic overall effects on weight control may exist [6].…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, low-fat (HCLF) diets produce an average weight loss of just 1.6 kg. [17] Another study found an average weight loss of 1.3 kg at 1 year and 0.2 kg at 2 years. [18] Even an intensive combined diet and physical activity intervention in severe obesity produced an average weight loss of only ~10 kg at 6 and 12 months.…”
Section: Discussionmentioning
confidence: 95%